Pengaruh Implementasi Kegiatan Belajar Daring Terhadap Mahasiswa Program Studi Ilmu Komputer Universitas Islam Negeri Sumatera Utara Medan - Fahrezy, M. Alif; Amiruddin, Amiruddin; Padang, Bermiko Kasah; Nainggolan, Ihsanul Hakim; Abdillah, Abdillah; Wifa, Azky; Suheri, M. (Jurnal Kridatama Sains dan Teknologi, 2024)
The COVID-19 pandemic has occurred globally since the end of 2019 and has changed significantly in various aspects of life, including in the education sector. To prevent the spread of the virus, many educational institutions in Indonesia were forced to stop face-to-face learning activities and switch to online learning. North Sumatra State Islamic University (UINSU) Medan is no exception in implementing this policy, especially for students in the Computer Science study program. The research results show that the implementation of online learning activities has a significant influence on students in the Computer Science study program at UINSU Medan. Adequate technological infrastructure and good digital competence support the effectiveness of online learning. However, not all students have the same access to technological infrastructure, so policies are needed that ensure equal access for all students. Online learning activities have great potential in increasing the flexibility and accessibility of education followed by technological infrastructure and digital competence. However, the psychological impact has a negative effect, indicating that stress and a sense of isolation reduce the effectiveness of online learning. Overall, the implementation of online learning activities in the Computer Science Study Program, North Sumatra State Islamic University, Medan, has had varying impacts on students. There are significant benefits in distraction and technical skills, but also challenges that need to be overcome especially regarding the quality of interactions and technological constraints. It is hoped that the effectiveness of online learning can be more optimal and provide a better learning experience for students of the Computer Science study program at UINSU Medan.